Australian schools and violent juveniles: safe haven or breeding grounds? - Monterosso, Stephen (ANZELA, 2011)
Contemporary focus on juvenile crime and violence within school environments is unsurprising as schools provide an arena in which juvenile violence is both perpetrated and controlled. A precise definition of school violence is not without difficulty however given the many and varied examples of violence in school based settings. Australia schools are in the main safe places compared with many overseas locations notwithstanding several well publicised school fatalities that have occurred recently. A thorough understanding of the true extent of school violence is problematic however as structural obstacles in available violent crime figures and statistics relevant to schools have impeded meaningful analysis of the scope of the problem within Australian. This paper will explore both the nature of school violence and its prevalence within the Australian jurisdiction.